Financial Distress, CEO Overconfidence dan Tax Avoidance - Jevita, Astria; Siregar, Sylvia Veronica (E-Jurnal Akuntansi; Vol 33 No 6 (2023)DO - 10.24843/EJA.2023.v33.i06.p01, 2023)
This study aims to analyze the impact of financial distress and CEO Overconfidence on tax avoidance. The worse a company's financial difficulties, the more likely the company is to engage in tax evasion. CEOs who are overly confident tend to take tax evasion actions. The population in this study are Indonesian companies listed on the IDX from all industrial sectors. This research was conducted in all industrial sectors in Indonesia with a total sample of 353 non-financial companies and included the conditions of the pandemic (Covid-19) used as a moderating variable. Data analysis was performed using multiple linear regression panel data and panel data regression moderation. The results showed that financial distress had a positive and significant effect on corporate tax avoidance, while CEO overconfidence had no effect on corporate tax avoidance. The more the company is in a dangerous condition of capital adequacy, the greater the level of tax evasion committed by the company. This research is useful for identifying risks and conducting tighter supervision of tax avoidance actions. Keywords: Financial Distress; CEO Overconfidence; Tax Avoidance; Effective Tax Rate (ETR)